2014
DOI: 10.12998/wjcc.v2.i8.345
|View full text |Cite
|
Sign up to set email alerts
|

Tree stand falls: A persistent cause of neurological injury in hunting

Abstract: Falls from hunting tree stands are still common, with a high rate of neurological injury. Compared to a decade ago we have made no progress in preventing these neurological injuries, despite an increase in safety advances. Neurosurgeons must continue to advocate for increased safety awareness and participate in leadership roles to improve outcomes for hunters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…Our results support recent evidence from the USA that falls, as opposed to direct injury from firearm projectiles, are the principal cause of nonfatal hunting-related injuries [ 10 , 12 ]. In this study, over almost a third of hunting-related injuries were associated with falls but not all from elevated tree stands; some injuries were sustained from falls whilst hunting in difficult terrain.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our results support recent evidence from the USA that falls, as opposed to direct injury from firearm projectiles, are the principal cause of nonfatal hunting-related injuries [ 10 , 12 ]. In this study, over almost a third of hunting-related injuries were associated with falls but not all from elevated tree stands; some injuries were sustained from falls whilst hunting in difficult terrain.…”
Section: Discussionsupporting
confidence: 90%
“…In the USA, falls from tree stands may account for up to two-thirds of all hunting-related injuries and 8% result in permanent neurological injury or death [ 7 , 8 ]. Common causes for falls from tree stands include poor tree stand construction, loss of balance, and falling asleep in the hide [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The text expression pattern in this study was informed by suggestions and methods from other studies (8, 9), preliminary exploratory chart reviews, and clinical consensus among study investigators. As done in some previous studies (6, 16, 17), supplemental diagnostic codes indicative of an external injury caused by an accidental fall from an elevated position (i.e., E880.9, E881.0, E881.1, E882, E884.9, E929.3) were initially evaluated for possible integration into the final case-finding logic. However, preliminary chart reviews revealed that these fall codes were not commonly present, thus were not considered in our case-finding logic.…”
Section: Methodsmentioning
confidence: 99%